Monitoring effects of sleep extension and restriction on endurance performance using heart rate indices - Roberts, S. S.; Aisbett, B.; Teo, W. P.; Warmington, S. (The Journal of Strength and Conditioning Research, 2022)
Heart rate (HR) indices are useful for monitoring athlete fatigue or "readiness to perform." This study examined whether HR indices are sensitive to changes in readiness following sleep restriction (SR) and sleep extension (SE). Nine athletes completed a crossover study with 3 conditions: SR, normal sleep (NS), and SE. Each condition required completion of an endurance time trial (TT) on 4 consecutive days (D1-D4). Athletes slept habitually before D1; however, time in bed was reduced by 30% (SR), remained normal (NS), or extended by 30% (SE), on subsequent nights (D1-D3). Daily resting HR and HR variability were recorded. The maximal rate of HR increase and HR recovery was determined from a constant-load test before TTs. Exercise intensity ratios incorporating mean HR, mean power (W), and perceived exertion (RPE) were recorded at steady state during constant-load tests (W:HRSS) and during TTs (W:HRTT, RPE:HRTT). Compared with D4 of NS, RPE:HRTT was lower on D4 of SE (p = 0.008)—when TT performances were faster. Compared with D1 of SR, RPE:HRTT was higher on D3 and D4 of SR (p < 0.02). Moderate correlations were found between percentage changes in W:HRTT and changes in TT finishing time in SR (r = -0.67, p = 0.049) and SE (r = -0.69, p = 0.038) conditions. Intensity ratios incorporating mean HR seem sensitive to effects of sleep duration on athlete readiness to perform. When interpreting intensity ratios, practitioners should consider potential effects of prior sleep duration to determine whether sleep-promoting interventions are required (e.g., SE).